2019
DOI: 10.1177/1528083718825316
|View full text |Cite
|
Sign up to set email alerts
|

The effects of UV degradation on the physical, thermal, and morphological properties of industrial nylon 66 conveyor belt fabrics

Abstract: In this study, nylon 66 industrial fabrics (used in the conveyor belts) were exposed artificially to the accelerated ultraviolet rays and the degradation mechanism was evaluated using spectral, thermal, and morphological analyses. The fabric samples were exposed to six different exposure times in a UV chamber and tensile tests were carried out in the main and bias (45°) directions. The results showed that the shear modulus was reduced in the early stages covering 4 h of the UV radiation because of the linkages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Different from tests in the UV cross-linker, the samples were exposed to UV irradiation continuously for a significantly longer time of 72 h, corresponding to an energy level that could affect the structural integrity of nylon. A similar level of UV irradiation has been observed to induce photooxidation of nylon [38,39], which could result into remarkable losses of mechanical strength [7].…”
Section: Testing Proceduresmentioning
confidence: 75%
See 1 more Smart Citation
“…Different from tests in the UV cross-linker, the samples were exposed to UV irradiation continuously for a significantly longer time of 72 h, corresponding to an energy level that could affect the structural integrity of nylon. A similar level of UV irradiation has been observed to induce photooxidation of nylon [38,39], which could result into remarkable losses of mechanical strength [7].…”
Section: Testing Proceduresmentioning
confidence: 75%
“…During their life cycle, webbing structures are often subjected to long-term exposures to sunlight. The ultra-violet (UV) component of sunlight can damage the integrity of webbings made of polymeric fabrics, such as nylon, Kevlar, and polyester, causing degradation in toughness [5], along with tensile [6] and shear strengths [7]. Quantifying the amount of UV energy absorbed by the material is a pivotal aspect of the health monitoring of webbing structures.…”
Section: Introductionmentioning
confidence: 99%
“…A recent photocatalytic study reported greater MF degradation efficiency when 254 nm was applied compared to 365 nm (Lee et al, 2020). The application of UV-C lamps (254 nm) resulted in higher carbonyl index values and FTIR results showed more intense peak bands ≈1630 cm −1 compared to the application of UV-A, which correspond to the carbonyl group of the amide groups (NH-C=O) on the fibres after oxidation (Moezzi et al, 2020) (Fig. 5).…”
Section: Effect Of Uv Irradiationmentioning
confidence: 94%
“…The band ≈1630 cm −1 may correspond to the carbonyl group from amide groups (NH-C=O) and the reference peak selected was the most intense band from the CH 2 stretching. The reference blank was selected assuming that CH groups may undergo less oxidation and may remain constant [76]. (Figure 12).…”
Section: Changes Of Chemical Propertiesmentioning
confidence: 99%